2020
DOI: 10.1038/s41396-020-0706-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophy in the earliest gut: a single-cell view of heterotrophic carbon and nitrogen assimilation in sponge-microbe symbioses

Abstract: Sponges are the oldest known extant animal-microbe symbiosis. These ubiquitous benthic animals play an important role in marine ecosystems in the cycling of dissolved organic matter (DOM), the largest source of organic matter on Earth. The conventional view on DOM cycling through microbial processing has been challenged by the interaction between this efficient filter-feeding host and its diverse and abundant microbiome. Here we quantify, for the first time, the role of host cells and microbial symbionts in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 84 publications
(161 reference statements)
7
120
0
Order By: Relevance
“…However, compound-specific (e.g. stable isotope) tracer studies have shown that both sponge cells and associated microbes are involved in organic matter assimilation [36,37], and recent nanoscale secondary ion mass spectrometry (NanoSIMS) studies have confirmed that both host choanocytes (sponge filtering cells) and symbionts can directly assimilate DOM [8,38]. It has been hypothesised that microbially assimilated DOM will be translocated to the host [39], while hostprocessed POM will be recycled by microbial symbionts [13], but these metabolic interactions have not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…However, compound-specific (e.g. stable isotope) tracer studies have shown that both sponge cells and associated microbes are involved in organic matter assimilation [36,37], and recent nanoscale secondary ion mass spectrometry (NanoSIMS) studies have confirmed that both host choanocytes (sponge filtering cells) and symbionts can directly assimilate DOM [8,38]. It has been hypothesised that microbially assimilated DOM will be translocated to the host [39], while hostprocessed POM will be recycled by microbial symbionts [13], but these metabolic interactions have not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific research is advancing in the measurement of nutrient fluxes in several species of sponges. However, sometimes, even if a given flux is measured, the pathway of the uptake and release of a given compound and the involvement of the sponge cells versus its symbiotic organisms can be difficult to discriminate (Rix et al, 2020).…”
Section: Methodological Approachmentioning
confidence: 99%
“…In a day, a dense sponge ground can efficiently clear all bacteria found in a water column up to 170 m deep . Sponges also consume large quantities of DOM, constituting up to 97 percent of sponge diet (Rix et al, 2020). A recent study has demonstrated that DOM is taken up both by symbiontic bacteria and sponge cells (Rix et al, 2020).…”
Section: Evidence On the Effects Of Water-pumping Activity Of Deep-sementioning
confidence: 99%
“…Eight of these unique genes encode proteins potentially involved in the transport and metabolism of sugars. Sugar transport/uptake plays an important role in symbiotic interactions [60][61][62][63]. Therefore, the presence of these genes would suggest that sugars are similarly important to the spirochete-sponge interaction.…”
Section: Identification Of Unique Genes In Ca L Rolihlahla Relativementioning
confidence: 99%